ECONOMIC AND ENVIRONMENTAL ASPECTS ASSOCIATED WITH THE TECHNOLOGIES FOR ELECTRICITY PRODUCTION FROM CONVENTIONAL SOURCES AND MEASURES TO MITIGATE THE PRODUCED IMPACTS - PAUL CALANTER (Global Economic Observer)
The electricity sector represents the sector with the greatest impact in terms of producing climate change, mainly due to the greenhouse gas emissions generated through the burning of fossil fuels. It is not however the only negative aspect associated to the classic technologies of electricity production. This paper aims to assess the economic and environmental aspects associated to the technologies for the electricity production from conventional sources and as a conclusion of the research it will also propose certain specific measures designed to mitigate their impacts. Therefore, the analysis will focus on economic issues, such as limited resources of fuels and the significant fluctuation in fuel prices, low energy efficiency, environmental protection expenditures and health issues as a result of the pollution generated by the electricity production and environmental aspects related primarily to the burning of fossil fuels, but also to extraction, transport and storage, aspects concerning the management of waste generated by the energy sector or to the risks associated with the process of producing electricity. In the final part of the paper a few measures will be proposed to mitigate the impact on the environment and economic development of such technologies, as well as increasing energy efficiency, promoting renewable sources of energy, carbon dioxide capture and storage, limiting deforestation, afforestation or the prevention of accidents in the energy sector.